PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP SEBAGAI IMPLEMENTASI GOOD GOVERNANCE BADAN PERTANAHAN KABUPATEN DOMPU - Taufik Fauzi Gustaman, (2022)
Complete Systematic Land Registration is the first land registration that is carried out en masse in the context of issuing land rights certificates. This thesis aims to determine the implementation of the principles of good governance by the National Land Agency of Dompu Regency in the implementation of the PTSL program for the 2020 fiscal year. This research is an empirical juridical research. The problem approach used is socio legal. The legal materials used are primary and secondary which were collected through interviews and supported by literature studies. The data analysis used is qualitative analysis with descriptive analysis writing. Complete Systematic Land Registration for the 2020 fiscal year is carried out through the stages of Planning, Counseling, Collection of Juridical Data and Physical Data, Land Inspection, Bookkeeping of Rights, and Issuance of Certificates. This is in accordance with the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 6 of 2018 concerning the Implementation of Complete Systematic Land Landing. To support the implementation of the PTSL program, the National Land Agency of Dompu Regency has also implemented the principles of good governance in the form of the General Principles of State Administration (AAUPB) as stated in Law Number 23 of 2014 concerning Regional Government. so that in the implementation of the PTSL program for the 2020 fiscal year, it has met the previously determined target, which has succeeded in issuing 1500 certificates to be submitted to the PTSL applicant community in the Dompu Regency area. (Valid)